2019
DOI: 10.5194/acp-2018-1353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iodine speciation and size distribution in ambient aerosols at a coastal new particle formation hotspot of China

Abstract: <p><strong>Abstract.</strong> Intense new particle formation (NPF) events were observed in the coastal atmosphere during algae growth and farming season at Xiangshan Gulf of east China coast. High nucleation-mode iodine concentrations measured by ultra-performance liquid chromatography coupled with quadruple time-of-flight mass spectrometry (UPLC/Q-TOF-MS) confirmed that the NPF events were induced by iodine species. Farmed microalgae, as well as wild algae, could be a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…NPF has been long observed in the coastal regions of Ireland, Scotland, France, Australia, Antarctica and China (Bigg & Turvey, ; Flanagan et al, ; Huang et al, ; O'Dowd et al, ; Saiz‐Lopez et al, ; Wiedensohler et al, ; Y. Hu et al, ). The North Atlantic Aerosols and Marine Ecosystems Study NAAMES campaign has elucidated the contribution of NPF involving sulfur to CCN concentrations in the marine atmosphere (Sanchez et al, ).…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…NPF has been long observed in the coastal regions of Ireland, Scotland, France, Australia, Antarctica and China (Bigg & Turvey, ; Flanagan et al, ; Huang et al, ; O'Dowd et al, ; Saiz‐Lopez et al, ; Wiedensohler et al, ; Y. Hu et al, ). The North Atlantic Aerosols and Marine Ecosystems Study NAAMES campaign has elucidated the contribution of NPF involving sulfur to CCN concentrations in the marine atmosphere (Sanchez et al, ).…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
“…Vaattovaara et al () observed that organics also contribute to the growth of freshly formed coastal (iodine) particles. Recently H. Yu et al () have shown that previously unidentified organic iodine compounds, such as iodate, aromatic iodinecompounds, iodoacetic acid or iodopropenoic acid, and iodide–organic adducts can also participate in NPF in an iodine hotspot at the east coast of China.…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%